2023
DOI: 10.1002/hep.32663
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of calcium dynamics in zebrafish hepatocytes

Abstract: Hepatocytes were the first cell-type for which oscillations of cytoplasmic calcium levels in response to hormones were described. Since then, investigation of calcium dynamics in liver explants and culture has greatly increased our understanding of calcium signaling. A bottleneck, however, exists in observing calcium dynamics in a non-invasive manner due to the optical inaccessibility of the mammalian liver. Here we take advantage of the transparency of the zebrafish larvae to develop a setup that allows in vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…We found that at 4 dpf, zebrafish display very little hepatic lipid droplets, while at 6 dpf, without exogenous feeding, zebrafish enter a fasting state with robust hepatic steatosis (Fig. 2A) (13). Following 6 dpf, hepatic lipid droplets decreased (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We found that at 4 dpf, zebrafish display very little hepatic lipid droplets, while at 6 dpf, without exogenous feeding, zebrafish enter a fasting state with robust hepatic steatosis (Fig. 2A) (13). Following 6 dpf, hepatic lipid droplets decreased (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…However, to our knowledge, it is not known if liver damage upon starvation progresses through a similar sequence of events. To investigate this, we turned to the zebrafish as a model system, where we and others have shown robust development of starvation-induced hepatic steatosis (13,14), similar to surface fish. We visualized hepatic lipid droplets in the Tg(fabp10a:EGFP) reporter line, which marks hepatocytes with green fluorescence, using Nile Red staining of neutral lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Maus et al (2017) observed that calcium homeostasis disruption led to the accumulation of lipid droplets in the liver, heart, and skeletal muscles of mice. Pozo-Morales et al (2023) found that the inhibition of calcium signaling accelerated the accumulation of starvation-related lipid droplets in the zebrafish liver through a genetically encoded calcium scavenger. Adequate mitochondrial function could maintain cardiovascular health and normal metabolism (Lane, 2006), as mitochondria constantly absorbed Ca 2+ to meet their physiological needs (Prudent et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium has also been widely used to reflect neuronal electric activities. Genetically encoded calcium indicators, GECIs, have been widely implemented into the zebrafish model for neural studies [ 147 , 148 , 149 ], cell migration [ 150 , 151 ], embryogenesis [ 152 , 153 ], insulin secretion from pancreatic beta cells [ 154 ], and many other biological processes [ 155 , 156 , 157 , 158 ]. Although calcium signals mimic electric signals, they are still different due to their additional function as a secondary messenger in various cell types.…”
Section: Genetically Encoded Tools That Can Be Used For Studying Deve...mentioning
confidence: 99%